The relationship between brain tissue properties and MRI signal - Blazejewska, Anna Izabella (2013)
Increased signal to noise ratio in high field magnetic resonance imaging (MRI) allows the acquisition of high resolution images and the development of the quantitative techniques for measuring tissue properties. This detailed information can provide a better understanding of the structure and function of the healthy brain but, more importantly, it can also provide methods for explaining pathological processes in neurodegenerative diseases. The work described in this thesis investigated iron and myelin content in the brain using 7T MRI. Multiple sclerosis (MS) is one of the most common demyelinating diseases. White matter (WM) lesions detected in MS with conventional MRI techniques show poor correlation with the disease progression. In this work investigation of degeneration of the WM as well as cortical and deep grey matter (GM) in MS and clinically isolated syndrome (CIS) suggestive of MS was performed using high resolution quantitative MRI techniques. Iron plays an important role in the physiological processes of the healthy brain, but its excessive accumulation in the particular brain structures accompanies neurodegeneration in Parkinson’s disease (PD). Studies analysing anatomy and quantitative properties of these structures, in vivo and post mortem, comparing PD patients with healthy controls are presented in this thesis. Investigation related to iron is supported by the simulations aimed at understand the effects of tissue microstructure related to iron on the MR signal. The presented analyses provide a better understanding of the complex dependencies of different MR contrasts on myelin and iron content.